Postklasyczna groza. Przeobrażenia fuzji gatunkowej survival horroru - Staszenko-Chojnacka, Dominika (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This article provides an introduction to the study of the transformation of the survival horror genre. The author discusses the genre determinants of horror games from the historical perspective, draw- ing particular attention to the moment when the classic survival horror formula emerged. She also describes the changes over the years that led both to the need to update the genre framework and to the division into classic and post-classic horror games. She also analyses the mechanics typical of contemporary productions using horror elements.